Factors Influencing Repeat Cash Waqf Contribution For Islamic Philanthropy - Fuadah Johari; Syadiyah Abdul Shukor; Muhammad Ridhwan Ab. Aziz; Nursilah Ahmad; Zurina Kefeli@ Zulkefli; Mohammad Haji Alias; Kalsom Abd Wahab; Fauzi Abu Hussin; Patmawati Ibrahim (Universiti Teknologi MARA, 2024)
Management & Accounting Review (MAR), [S.l.], v. 14, n. 2, p. 55-78, dec. 2015